PENGEMBANGAN SCIENCE IN BOX FLUIDA STATIS UNTUK PEMBELAJARAN IPA SMP - Muhammad Anshory; Abdurrahman Abdurrahman; Wayan Suana (Jurnal Pembelajaran Fisika, 2015)
This development research aimed to create a Science in Box Static Fluid that is a low-cost materials then collected in one box to teach four static fluid concepts through hands-on experiment on class. The development steps of this research included needs analysis, formulating learning goals, formulating each materials, arranging the instruments of evaluation, writing the script of media, the initial product, expert validation, field experiment, and Science in Box Static Fluid as the last product completed with worksheets and instructions. The result of the expert validation showed that Science in Box Static Fluid was suitable to use as experiment kit. The result of field experiment showed that the score of attractiveness, easiness, and helpfulness were 3.27 (very attractive), 3.12 (easy to use), and 3.55 (very useful) respectively, and 84.21% of students reached the passing grade (KKM). It can be concluded that Science in Box Static Fluid is effective to use as media of learning.Keywords: development, experiment, science in box, science learning, static fluidPenelitian pengembangan ini bertujuan untuk menghasilkan Science in Box Fluida Statis berupa kumpulan peralatan murah lalu dikumpulkan dalam satu box untuk membelajarkan empat konsep fluida statis melalui praktikum langsung di kelas. Tahapan pengembangan meliputi analisis kebutuhan, perumusan tujuan pembelajaran, perumusan butir-butir materi, penyusunan instrumen evaluasi, penulisan naskah media, produk awal, validasi ahli, uji coba lapangan, dan produk akhir berupa Science in Box Fluida Statis dilengkapi dengan LKS dan petunjuk penggunaan. Hasil uji ahli menunjukkan Science in Box Fluida Statis layak digunakan sebagai alat praktikum. Hasil uji lapangan menunjukan nilai kemenarikan 3,27 (sangat menarik), kemudahan 3,12 (mudah digunakan) dan kemanfaatan 3,55 (sangat bermanfaat), serta 84,21% siswa tuntas KKM. Dapat disimpulkan bahwa Science in Box Fluida Statis efektif digunakan sebagai media pembelajaran.Kata kunci: fluida statis, pembelajaran IPA, pengembangan, praktikum,science in box